A Three-Phase Discourse Analysis of Student Business Presentations - Sazdovska, Jasmina (Working Papers in Language Pedagogy, 2007)
This paper is a discourse analysis study of three phases of the development of students participating in a 15-week Presentation Skills course. The four second-year business students were recorded performing presentations before instruction, in the middle of the course and at the end of the semester. The recordings were transcribed, coded and analysed to determine the changes in the structure of the content and the communicative strategies employed by the students. The results indicate that over time the participants develop a greater ability to structure their talks more clearly, yet elaborately, and signal the arrangement more overtly with the aid of organisational indicators. The functions that the students employ tend to be predominantly neutral and informative, but there is a shift to more positive, cooperative strategies in later stages. These results contribute to more effective instruction, help further develop the coding system and can represent a starting point for a more in-depth analysis of the genre.